Prevalence and risk factors of depression in rural Chinese hemodialysis patients during the COVID-19 pandemic: a multicenter cross-sectional study - Zhaoqi Liu; Juhua Lin; Zhiqiang Chen; Rugang Li; Junping Tang; Quan Liu; Lin Ning; Min He (Frontiers in Psychology)
PurposeThis study aimed to assess the prevalence and risk factors of depression among maintenance hemodialysis (MHD) patients in rural China during the COVID-19 pandemic.MethodsA cross-sectional survey was conducted in 14 hemodialysis centers in northern Guangdong Province from April to October 2021. Depression was evaluated using the Self-Rating Depression Scale. Multivariate logistic regression analysis was employed to identify associated factors.ResultsOf the 450 MHD patients enrolled, 160 (35.6%) met the criteria for depression, with 91.8% cases being of mild severity. After adjusting for demographic, dialysis-related, laboratory, pandemic-associated lifestyle changes, and psychological variables, discomfort during dialysis [Odds ratio (OR) 1.654, 95% Confidence Interval (CI) 1.105–2.474] and infection worry (OR 1.719, 95% CI 1.121–2.636) were significantly associated with an increased risk of depression. In contrast, college education was linked to a lower risk (OR 0.456, 95% CI 0.245–0.846).ConclusionDuring the COVID-19 pandemic in rural China, mild depression were common among MHD patients. Mandatory behavioral interventions did not contribute to depression, while discomfort during dialysis and infection worry emerged as risk factors, and college education was associated with a lower risk.